Analysis of Facebook Pro User Satisfaction Using the PIECES Method - 'alimah, Muta; Megawati, Megawati; Angraini, Angraini; Fronita, Mona; Zarnelly, Zarnelly (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
Facebook Pro is a feature developed by Meta to provide a professional experience for users in managing content and interactions on the Facebook platform. However, user satisfaction with this feature has not been extensively studied, particularly in the city of Pekanbaru. This study aims to analyze the level of user satisfaction with Facebook Pro in Pekanbaru using the PIECES framework, which consists of six key variables: Performance, Information and Data, Economy, Control and Security, Efficiency, and Service. The research findings indicate that the satisfaction scores for each variable are as follows: Performance (3.70), Information and Data (3.84), Economy (3.37), Control and Security (3.48), Efficiency (3.58), and Service (3.70). Most of these fall under the “satisfied” category, with the exception of Economy, which is rated as “moderately satisfied.” Overall, the average satisfaction score was 3.61, placing user satisfaction within the “satisfied” category. These results suggest that most users feel comfortable and supported by the features and services provided by Facebook Pro. However, the relatively lower scores in the Economy and Control and Security dimensions highlight areas where users are experiencing challenges, indicating a need for improvement in those aspects.